2016
DOI: 10.1002/cne.24018
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of whisker‐mediated somatosensation in mammals: Sensory processing in barrelless S1 cortex of a marsupial, Monodelphis domestica

Abstract: Movable tactile sensors in the form of whiskers are present in most mammals, but sensory coding in the cortical whisker representation has been studied almost exclusively in mice and rats. Many species that possess whiskers lack the modular “barrel” organization found in the primary somatosensory cortex (S1) of mice and rats, but it is unclear how whisker-related input is represented in these species. We used single-unit extracellular recording techniques to characterize receptive fields and response propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 95 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, our findings resemble some forms of plasticity previously reported in the S1 whisker representation, which are functionally distinct from Hebbian forms of plasticity (for review, see Feldman and Brecht, 2005) typically observed in studies involving manipulations that create competition among sensory inputs within the whisker system (e.g., deprivation of a subset of whisker inputs though trimming, plucking, or follicle lesion). Polley et al (2004) found that prolonged exposure of rats to complex, naturalistic environments in adulthood resulted in the contraction of the functional representation of individual whiskers, suppression of whisker-evoked responses, and smaller, sharper receptive fields for neurons in S1. Further, when adult rats were allowed brief periods of whisker-guided exploration in a novel environment after deprivation of all but a single whisker, the direction of Hebbian plasticity was reversed, causing a contraction of the functional representation of the spared whisker rather than its expansion (Polley et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, our findings resemble some forms of plasticity previously reported in the S1 whisker representation, which are functionally distinct from Hebbian forms of plasticity (for review, see Feldman and Brecht, 2005) typically observed in studies involving manipulations that create competition among sensory inputs within the whisker system (e.g., deprivation of a subset of whisker inputs though trimming, plucking, or follicle lesion). Polley et al (2004) found that prolonged exposure of rats to complex, naturalistic environments in adulthood resulted in the contraction of the functional representation of individual whiskers, suppression of whisker-evoked responses, and smaller, sharper receptive fields for neurons in S1. Further, when adult rats were allowed brief periods of whisker-guided exploration in a novel environment after deprivation of all but a single whisker, the direction of Hebbian plasticity was reversed, causing a contraction of the functional representation of the spared whisker rather than its expansion (Polley et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…After 4x rinsing in PBS, secondary antibody Alexa Flour 488 goat anti‐Mouse (RRID:AB_2534088; diluted in PBS‐Tx 0.1%) was added for 6 hr at RT. The mouse anti‐Parvalbumin generated against purified frog muscle Parvalbumin is highly specific and recognizes a single band of ∼12 kDa in Western blots of lysed brain tissue, the molecular weight of Parvalbumin (Ramamurthy & Krubitzer, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we examined the role of two sets of facial whiskers -the mystacial whiskers (on the snout) and genal whiskers (on the cheek; Ramamurthy and Krubitzer, 2016) in guiding tactile-based decisions in early blind and sighted opossums, and measured their behavioral discrimination sensitivity to texture cues. To our knowledge, this is the first psychometric investigation of texture discrimination in a marsupial.…”
Section: Introductionmentioning
confidence: 99%